Low-polymerization-degree carbon nitride nanosheet containing partial supramolecular chain, preparation method of low-polymerization-degree carbon nitride nanosheet and application of low-polymerization-degree carbon nitride nanosheet in simultaneous hydrogen production and oxygen production by photocatalytic water decomposition
By preparing low-polymerization carbon nitride nanosheets containing partial supramolecular chains, the serious problem of photogenerated carrier recombination of photocatalysts is solved, and efficient photocatalytic decomposition of water hydrogen production is achieved.
Patent Information
- Application Number
- CN202411703922.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The serious problem of existing photocatalysts in photogenerated carrier recombination leads to inefficient efficiency in photocatalyzed decomposition of water to prepare hydrogen.
By pre-synthesis of supramolecular precursors, connecting melamine and cyanuric acid using hydrogen bonds, controlling the calcination temperature to optimize the degree of polymerization of carbon nitride, and preparing oligopolymerization carbon nitride nanosheets containing part of supramolecular chains.
The efficient photocatalytic hydrogen production performance of the photocatalyst is achieved, which can catalyze the decomposition of water under full spectrum conditions and simultaneously produce hydrogen and oxygen, and has a stable and efficient single-photon system full decomposition ability.
Smart Images

Figure CN119500230A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of hydrogen energy preparation, and relates to a photocatalytic clean preparation technology for hydrogen energy, namely, a technology for cheaply preparing hydrogen energy by photocatalytically decomposing water under full-spectrum conditions, and particularly relates to providing a low-polymerization carbon nitride nanosheet containing a partial supramolecular chain, a preparation method, and an application of photocatalytically decomposing water to simultaneously produce hydrogen and oxygen, which is beneficial to the industrial application of photocatalytically decomposing water to produce hydrogen. Background Art
[0002] With the advancement of global modernization and industrialization, human society's demand for energy is increasing day by day. Energy and environment have become the two most pressing issues, which greatly threaten the survival and development of human society. Therefore, in order to solve these two challenging problems, all countries have vigorously promoted the strategy of developing sustainable renewable energy utilization to promote the low-carbonization of the global energy industry and social development, which is also the goal of my country's energy technology field. Hydrogen energy (H2) is an energy source with high energy density, no pollution, no toxicity, easy to store and transport, and the combustion product of hydrogen is water, which can be decomposed to produce hydrogen, so it is considered to be an ideal clean energy. Decomposing water to produce hydrogen through semiconductor photocatalysts and realizing the green conversion of light to hydrogen is currently a promising clean energy conversion technology. The core point of this technology is semiconductor photocatalysts, so the most critical thing is to prepare efficient, stable, pollution-free and economical photocatalysts.
[0003] There are three key steps for photocatalytic decomposition of water to produce hydrogen: when the semiconductor catalyst is irradiated with light whose energy is greater than its band gap, it is excited by the light to produce electron-hole pairs; the separated electron-hole pairs are transferred from the inside of the catalyst to the surface of the catalyst, and some of the electron-hole pairs will recombine; the electrons that migrate to the surface will undergo a reduction reaction with water to produce hydrogen, while the holes will undergo an oxidation reaction with water. For a complete water decomposition reaction to produce hydrogen and oxygen, in order to ensure sufficient redox driving force, the photocatalytic band gap needs to be at least greater than 1.23 eV. In addition, this is a four-electron process (2H2O+4e - +4h + →2H2+O2), the process is relatively complex and is a typical uphill reaction with an increase in Gibbs free energy. The Gibbs free energy before and after the reaction reaches 237 kJ mol -1. In addition to the above-mentioned kinetic and thermodynamic factors, the adsorption and desorption process of the interface is also a key constraint. For the hydrogen (oxygen) evolution reaction, increasing the adsorption capacity for protons (water) further increases the probability of proton (water) reduction (oxidation) to generate hydrogen (oxygen); conversely, if the adsorption capacity for hydrogen (oxygen) is strong, hydrogen (oxygen) is not easy to desorb, thereby hindering the continued progress of the photocatalytic reaction. In the complete water decomposition reaction, in addition to the above process, the undesorbed hydrogen and oxygen in the system may undergo a reverse reaction to generate water, reducing the hydrogen production activity of the complete water decomposition reaction. For the surface reaction mechanism of photocatalysts, in addition to simple adsorption and desorption processes, more attention should be paid to the influence of surface atoms on the reaction. For example, in the complete water decomposition reaction, how to easily achieve the breaking of the HO bond and promote the formation of HH bonds and OO bonds is the essential reason for improving the activity of complete water decomposition; at the same time, how to avoid the reverse reaction and clarify the core factors of the reverse reaction will help to further design photocatalysts.
[0004] According to existing research and foundation, among many types of photocatalyst materials, the graphite phase carbon nitride (g-C3N4) photocatalyst has a band gap width of about 2.7 eV, can completely decompose water to produce hydrogen and oxygen under visible light, and is non-toxic, cheap, simple to prepare, and has abundant and stable raw materials. It has great application prospects and research value. However, since the molecular structure of carbon nitride is mainly composed of triazine structural units connected by amino groups, this will form an internal highly symmetrical structure, which seriously hinders the migration of internal photogenerated carriers, thereby reducing the photocatalytic hydrogen production activity of CN. However, it is difficult to optimize the molecular structure of CN by traditional methods. Most of them are incorporated into the molecular structure in the form of heteroatoms, showing the characteristics of single groups and atoms. It is difficult to retain the characteristics of individual molecules, and the optimization of the surface is slightly insufficient. Recently, according to the report of Lotsch of the University of Munich, by controlling the synthesis temperature of melon, low molecular weight CN was synthesized, emphasizing the role of defects (chain end groups) in improving the catalytic activity of CN, and also indicating that there is sufficient potential to improve the photocatalytic activity of CN essentially through the selective synthesis of active phases. At present, there are two main nodes for the synthesis of CN with traditional raw materials, one is the formation of melamine at 400℃, and the other is the formation of CN at 525℃. Therefore, temperature can change the molecular structure of CN and selectively retain the desired groups. Obviously, it is worth exploring if the basic framework structure of CN is synthesized first, the temperature is changed, and its molecular structure and surface interface reaction are optimized to achieve high photocatalytic complete water decomposition performance. Summary of the invention
[0005] In order to overcome the serious problem of photogenerated carrier recombination in the prior art, the purpose of the present invention is to provide a low-polymerization carbon nitride nanosheet containing partial supramolecular chains, a preparation method and an application of photocatalytic water decomposition to simultaneously produce hydrogen and oxygen, so as to achieve efficient photocatalytic hydrogen production by photocatalyst.
[0006] In order to achieve the above object, the present invention adopts the following technical solution: A method for preparing a low-polymerization carbon nitride nanosheet containing a partial supramolecular chain comprises the following steps: Adding melamine and cyanuric acid into a solvent, stirring after ultrasonication, and drying to obtain supramolecular precursor powder; The supramolecular precursor powder is calcined to obtain low-polymerization carbon nitride containing part of the supramolecular chains.
[0007] Furthermore, the ultrasonication time is 5-10 min, and the stirring time is 8-10 h.
[0008] Furthermore, the solvent is ethanol.
[0009] Furthermore, the molar ratio of melamine to cyanuric acid is 1:1.
[0010] Furthermore, the usage ratio of melamine to solvent is 0.04 mol:0.04 mol.
[0011] Furthermore, calcination was performed under N2 atmosphere.
[0012] Furthermore, the calcination temperature is 350-550 o C, time is 2 h.
[0013] Further, 3-5 o C / min heating rate to 400-550 o C.
[0014] A low-polymerization carbon nitride nanosheet containing partial supramolecular chains.
[0015] Application of low-polymerization carbon nitride nanosheets containing partial supramolecular chains in photocatalytic water decomposition and simultaneous production of hydrogen and oxygen.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses hydrogen bonds to connect melamine and cyanuric acid by pre-synthesizing supramolecular precursors, and controls the degree of polymerization of carbon nitride by controlling the calcination temperature, optimizes its own molecular structure, and strengthens the surface optimization of the photocatalytic water splitting reaction. The method of the present invention prepares a low-polymerization carbon nitride nanosheet containing a partial supramolecular chain for the first time, and optimizes the adsorption and dissociation of water molecules at the interface between the low-polymerization carbon nitride nanosheet and the reaction liquid by retaining a partial supramolecular oxygen-containing structure, thereby achieving high *H and *OH enrichment in the local environment and promoting the improvement of photocatalytic complete water splitting performance. Characterization results and theoretical analysis show that the oxygen-containing functional groups retained in the low-polymerization carbon nitride nanosheet promote its adsorption of water molecules, reduce the dissociation energy barrier of water molecules, achieve high *H and *OH in the local environment, and then promote the generation of hydrogen and oxygen. Therefore, under the synergistic effect of the oxygen-containing structure and the carbon nitride structure, the low-polymerization carbon nitride nanosheet obtains a stable and relatively efficient single-photon system complete water splitting ability.
[0017] Furthermore, by controlling the calcination temperature of the supramolecular precursor, the degree of conversion of cyanuric acid is controlled, and low-polymerization carbon nitride nanosheets with partially retained supramolecular structures are synthesized, achieving the coexistence of a supramolecular chain and a carbon nitride structure. The optimization of the carbon nitride chemical structure optimizes the interface reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is an infrared spectrum (FT-IR) of carbon nitride with different polymerization degrees in Examples 1-4 and Comparative Example 1; Figure 2 is the X-ray diffraction (XRD) diagram of carbon nitride with different polymerization degrees in Examples 1-4 and Comparative Example 1; Figure 3 are scanning electron microscope (SEM) images of carbon nitride with different polymerization degrees in Examples 1-4 and Comparative Example 1; Figure 4 It is a graph of complete decomposition of water to produce hydrogen under full spectrum conditions of carbon nitride with different polymerization degrees in Examples 1-4 and Comparative Example 1; Figure 5 This is a graph showing the complete decomposition of water to produce hydrogen under full spectrum conditions at different catalyst dosages in Example 1 and Examples 7-9 using low-polymerization carbon nitride containing partial supramolecular chains. DETAILED DESCRIPTION
[0019] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0020] The present invention discloses a method for preparing a low-polymerization carbon nitride nanosheet containing a partial supramolecular chain, comprising: Melamine and cyanuric acid were added to the ethanol solution and ultrasonicated for 5-10 min. o C and stirred vigorously for 8-10 h, the product was washed and vacuum dried to obtain supramolecular precursor powder, and the obtained supramolecular precursor powder was heated to 3-5 ℃ under N2 atmosphere. o C / min heating rate to 350-550 o After calcining C for 2-3 hours, low-polymerization carbon nitride containing part of the supramolecular chain is obtained, wherein the molar ratio of melamine to cyanuric acid is 1:1, and the amount ratio of melamine to ethanol is 0.04 mol:0.04 mol.
[0021] The present invention prepares low-polymerization carbon nitride containing partial supramolecular chains by controlling the polymerization temperature of carbon nitride on the basis of pre-synthesizing supramolecular precursors. The carbon nitride has good photocatalytic activity and can catalytically decompose pure water to produce hydrogen and oxygen simultaneously under full-spectrum conditions. The photocatalytic hydrogen production rate reaches 12.5 μmol h -1 The corresponding photocatalytic oxygen production rate reached 6.0 μmol h -1 After the dosage was optimized, the photocatalytic hydrogen production rate reached 28.3 μmol h -1 The corresponding photocatalytic oxygen production rate reached 13.5 μmol h -1 , and the quantum efficiency at 420 nm is 3.65%. The invention is simple to operate and has good repeatability, and provides a reliable solution for improving the efficiency of photocatalytic water decomposition to produce hydrogen and for the development and application of a new photocatalyst for simultaneous hydrogen and oxygen production.
[0022] The following is a specific implementation case.
[0023] Example 1 Step 1: Add 0.04 mol melamine (Mel) and 0.04 mol cyanuric acid (CU) to 100 mL anhydrous ethanol, disperse by ultrasonication for 5 min, and stir vigorously at 25°C for 8 h. Then centrifuge, wash with ethanol 2-3 times, and collect after vacuum drying at 60°C for 12 h. The white product finally obtained is the supramolecular precursor and is named CM.
[0024] Step 2: Grind the CM obtained in step 1 evenly and heat the ground powder at 400 o C calcined for 2 h (heating rate 3 o C / min), and then the obtained sample was ground and collected after cooling in the furnace. The obtained sample was the low-polymerization carbon nitride nanosheet CM-400 containing some supramolecular chains.
[0025] Step 3: Add the low-polymerization carbon nitride nanosheets CM-400 containing some supramolecular chains prepared in step 2 into 100 mL of pure water solution for photocatalytic water decomposition and simultaneous hydrogen and oxygen production test. The specific steps are as follows: 1) Add 10 mg of CM-400 photocatalyst to a reactor customized for the online system, add a total volume of 100 mL of pure solution, and add 3% Pt; 2) Before irradiation, use a vacuum pump to evacuate the system to remove the gas; 3) Turn on the magnetic stirrer and the xenon lamp.
[0026] Example 2 Step 1: Add 0.04 mol melamine (Mel) and 0.04 mol cyanuric acid (CU) to 100 mL anhydrous ethanol, disperse by ultrasonication for 5 min, and stir vigorously at 25 °C for 8 h. Then centrifuge, wash with ethanol 2-3 times, and collect after vacuum drying at 60 °C for 12 h. The white product finally obtained is the supramolecular precursor and is named CM.
[0027] Step 2: Grind the CM obtained in step 1 evenly and heat the ground powder at 450 o C calcined for 2 h (heating rate 3 o C / min), and then the obtained sample was ground and collected after cooling in the furnace. The obtained sample was low-polymerization carbon nitride CM-450 containing some supramolecular chains.
[0028] Step 3: Add the carbon nitride CM-450 with normal polymerization degree prepared in step 2 into 100 mL pure water solution to conduct photocatalytic water decomposition and simultaneous hydrogen and oxygen production test. The specific steps are as follows: 1) Add 10 mg of CM-450 photocatalyst to a reactor customized for the online system, add 100 mL of pure water solution with a total volume of 100 mL, and add 3% Pt; 2) Before irradiation, use a vacuum pump to evacuate the system to remove the gas; 3) Turn on the magnetic stirrer and the xenon lamp.
[0029] Example 3 Step 1: Add 0.04 mol melamine (Mel) and 0.04 mol cyanuric acid (CU) to 0.04 mol anhydrous ethanol, disperse by ultrasonication for 5 min, and stir vigorously at 25 °C for 8 h. Then centrifuge, wash with ethanol 2-3 times, and collect after vacuum drying at 60 °C for 12 h. The final white product is the supramolecular precursor and is named CM.
[0030] Step 2: Grind the CM obtained in step 1 evenly and place the ground powder under N2 atmosphere at 500 o C calcined for 2 h (heating rate 3 o C / min), and then the obtained sample was ground and collected after cooling in the furnace. The obtained sample was carbon nitride CM-500 with a higher degree of polymerization.
[0031] Step 3: Add the carbon nitride CM-500 with a high degree of polymerization prepared in step 2 into 100 mL of pure water solution for photocatalytic water decomposition and simultaneous hydrogen and oxygen production test. The specific steps are as follows: 1) Add 10 mg of CM-500 photocatalyst to the reactor customized for the online hydrogen production system, add pure water with a total volume of 100 mL, and add 3% Pt; 2) Before irradiation, use a vacuum pump to evacuate the system to remove the gas; 3) Turn on the magnetic stirrer and the xenon lamp.
[0032] Example 4 Step 1: Add 0.04 mol melamine (Mel) and 0.04 mol cyanuric acid (CU) to 100 mL anhydrous ethanol, disperse by ultrasonication for 5 min, and stir vigorously at 25°C for 8 h. Then centrifuge, wash with ethanol 2-3 times, and collect after vacuum drying at 60°C for 12 h. The white product finally obtained is the supramolecular precursor and is named CM.
[0033] Step 2: Grind the CM obtained in step 1 evenly and heat the ground powder at 550 o C calcined for 2 h (heating rate 3 o C / min), and then the obtained sample was ground and collected after cooling in the furnace. The obtained sample was high polymerization carbon nitride CM-550.
[0034] Step 3: Add the high-polymerization carbon nitride CM-550 prepared in step 2 into 100 mL of pure water solution to perform photocatalytic water decomposition and simultaneous hydrogen and oxygen production tests. The specific steps are as follows: 1) Add 10 mg of CM-550 photocatalyst to the reactor customized for the online hydrogen production system, add pure water with a total volume of 100 mL, and add 3% Pt; 2) Before irradiation, use a vacuum pump to evacuate the system to remove the gas; 3) Turn on the magnetic stirrer and the xenon lamp.
[0035] Example 5 Step 1: Add 0.04 mol melamine (Mel) and 0.04 mol cyanuric acid (CU) to 100 mL anhydrous ethanol, disperse by ultrasonication for 10 min, and stir vigorously at 25 °C for 10 h. Then centrifuge, wash with ethanol twice, and collect after vacuum drying at 60 °C for 12 h. The white product finally obtained is the supramolecular precursor and is named CM.
[0036] Step 2: Grind the CM obtained in step 1 evenly and heat the ground powder at 420 o C calcined for 2 h (heating rate 4 o C / min), and then the obtained sample was ground and collected after cooling in the furnace. The obtained sample was low-polymerization carbon nitride CM-420 containing some supramolecular chains.
[0037] Example 6 Step 1: Add 0.04 mol melamine (Mel) and 0.04 mol cyanuric acid (CU) to 100 mL anhydrous ethanol, disperse by ultrasonication for 7 min, and stir vigorously at 25 °C for 9 h. Then centrifuge, wash with ethanol 3 times, and collect after vacuum drying at 60 °C for 12 h. The final white product is the supramolecular precursor and is named CM.
[0038] Step 2: Grind the CM obtained in step 1 evenly and heat the ground powder at 480 o C calcined for 2 h (heating rate 5 o C / min), and then the obtained sample was ground and collected after cooling in the furnace. The obtained sample was low-polymerization carbon nitride CM-480 containing some supramolecular chains.
[0039] Example 7 Applications of photocatalytic water splitting to produce hydrogen and oxygen simultaneously: The process is the same as step 3 in Example 1, except that, in step 1), 20 mg of CM-400 photocatalyst is added to the reactor customized for the online system, a pure water solution with a total volume of 100 mL is added, and 3% Pt is added.
[0040] Example 8 Applications of photocatalytic water splitting to produce hydrogen and oxygen simultaneously: The process is the same as step 3 in Example 1, except that, in step 1), 30 mg of CM-400 photocatalyst is added to the reactor customized for the online hydrogen production system, a pure water solution with a total volume of 100 mL is added, and 3% Pt is added.
[0041] Example 9 Applications of photocatalytic water splitting to produce hydrogen and oxygen simultaneously: The process is the same as step 3 in Example 1, except that, in step 1), 40 mg of CM-400 photocatalyst is added to the reactor customized for the online hydrogen production system, a pure water solution with a total volume of 100 mL is added, and 3% Pt is added.
[0042] Comparative Example 1 Step 1: Add 0.04 mol melamine (Mel) and 0.04 mol cyanuric acid (CU) to 100 mL anhydrous ethanol, disperse by ultrasonication for 5 min, and stir vigorously at 25°C for 8 h. Then centrifuge, wash with ethanol 2-3 times, and collect after vacuum drying at 60°C for 12 h. The final white product is the supramolecular precursor and is named CM.
[0043] Step 2: Grind the CM obtained in step 1 evenly and heat the ground powder at 350 o C calcined for 2 h (heating rate 3 o C / min), and then the obtained sample was ground and collected after cooling in the furnace. The obtained sample was cyanuric acid and melamine supramolecular chain CM-350.
[0044] Step 3: Add the cyanuric acid and melamine supramolecular chain CM-350 prepared in step 2 into 100 mL of pure water solution for photocatalytic water decomposition and simultaneous hydrogen and oxygen production test. The specific steps are as follows: 1) Add 10 mg of CM-350 photocatalyst to the reactor customized for the online system, add a total volume of 100 mL of pure water solution, and add 3% Pt; 2) Before irradiation, use a vacuum pump to evacuate the system to remove the gas; 3) Turn on the magnetic stirrer and the xenon lamp.
[0045] Figure 1 The infrared spectra (FT-IR) of CM-350, CM-400, CM-450, CM-500 and CM-550 are shown in Figure 3. When the temperature is 350 °C, CM-350 still shows the stretching vibration peak characteristics similar to CM, but the peak intensity of CM-350 changes due to the change of hydrogen bond connection. After the temperature reaches 400 °C, the stretching vibration peaks of melamine-cyanurate disappear, and the peaks at 810, 1313, 1455, 1599 and 3200 cm -1 The characteristic peak representing 3-s-triazine monomer appears at 2900-3200cm -1 The hydrogen bonding characteristics between the two groups are still retained, which indicates that CM-400 is in a low-polymerization state. After the temperature reaches 550 ℃, the hydrogen bonding impurity peaks inside CM-550 disappear, and the characteristic peaks are concentrated at 3000-3500 -11100-1800 -1 and 800 cm -1 This indicates the presence of heptazine ring structure and amino structure. In summary, it is shown that CM-400 is a low-polymerization carbon nitride containing some supramolecular chains.
[0046] Figure 2 The X-ray diffraction (XRD) diagrams of CM-350, CM-400, CM-450, CM-500, and CM-550 are shown below. When the temperature is 350°C, melamine amides are generated by cyanuric acid in ammonia conditions, and the structure of hydrogen bonds changes, so that its crystal structure becomes the crystal structure of melamine-cyanurate. However, since the polycondensation reaction does not occur, the crystal structure of carbon nitride is not formed. As the temperature is further increased to 400°C, interlayer stacking of melem appears, and the typical interlayer stacking (002) peak of carbon nitride is manifested. However, since the degree of polymerization increases with the increase of temperature, the (100) peak of its atomic arrangement order slowly appears at a temperature of 450°C, and finally forms a relatively perfect melon structure of CM-550. This further proves that CM-400 is a low-polymerization crystal structure.
[0047] Figure 3 This is a SEM image of CM-350, CM-400, CM-450, CM-500, and CM-550. CM-350 is a larger and thicker sheet structure. The temperature reaches 400 o The C supramolecular crystal structural unit changes, the carbon nitride structure begins to form, a polymer phase is generated, and pores begin to appear. At the same time, the mass loss of the material accompanying the polycondensation process causes large gaps to appear in CM-400, turning the carbon nitride sheet into a concave sheet.
[0048] Figure 4 This is a graph of CM-350, CM-400, CM-450, CM-500, and CM-550 completely splitting water to produce hydrogen under full spectrum conditions. Under pure water conditions, the photocatalytic hydrogen production rate of CM-400 reached 12.5 μmol h -1 The corresponding photocatalytic oxygen production rate reached 6.0 μmol h -1 . It shows that low-polymerization carbon nitride containing partial supramolecular chains has excellent performance in completely splitting water to produce hydrogen.
[0049] Figure 5 This is the complete water decomposition hydrogen production diagram of CM-400 under full spectrum conditions with different catalyst dosages. When the mass of CM-400 reaches 30 mg, the hydrogen production rate in pure water reaches 28.3 μmol h -1 The corresponding photocatalytic oxygen production rate reached 13.5 μmol h-1 .
[0050] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing low-polymerization carbon nitride nanosheets containing partial supramolecular chains, characterized in that: The following steps are involved: Adding melamine and cyanuric acid into a solvent, stirring after ultrasonication, and drying to obtain supramolecular precursor powder; The supramolecular precursor powder is calcined to obtain low-polymerization carbon nitride containing part of the supramolecular chains.
2. The method for preparing low-polymerization carbon nitride nanosheets containing partial supramolecular chains according to claim 1, characterized in that: The ultrasonic time is 5-10 min, and the stirring time is 8-10 h.
3. The method for preparing low-polymerization carbon nitride nanosheets containing partial supramolecular chains according to claim 1, characterized in that: The solvent is ethanol.
4. The method for preparing low-polymerization carbon nitride nanosheets containing partial supramolecular chains according to claim 1, characterized in that: The molar ratio of melamine to cyanuric acid is 1:
1.
5. The method for preparing low-polymerization carbon nitride nanosheets containing partial supramolecular chains according to claim 1, characterized in that: The dosage ratio of melamine to solvent is 0.04 mol:0.04 mol.
6. The method for preparing low-polymerization carbon nitride nanosheets containing partial supramolecular chains according to claim 1, characterized in that: Calcination was carried out under N2 atmosphere.
7. The method for preparing low-polymerization carbon nitride nanosheets containing partial supramolecular chains according to claim 1, characterized in that: The calcination temperature is 350-550 o C, time is 2 h.
8. The method for preparing low-polymerization carbon nitride nanosheets containing partial supramolecular chains according to claim 7, characterized in that: 3-5 o C / min heating rate to 400-550 o C.
9. A low-polymerization carbon nitride nanosheet comprising partial supramolecular chains prepared according to the method of any one of claims 1 to 8.
10. Use of low-polymerization carbon nitride nanosheets containing partial supramolecular chains prepared by the method according to any one of claims 1 to 8 in photocatalytic water decomposition for simultaneous production of hydrogen and oxygen.
Citation Information
Patent Citations
Core-shell carbon nitride material and preparation method thereof
CN106622326A
Salt-assisted preparation method of three-dimensional graphite phase carbon nitride containing cyano groups
CN107473191A
Carbon nitride nano material as well as preparation method and application thereof
CN109734060A
Preparation method and application of spherical crystalline carbon nitride with heptazine ring structure
CN114920219A
Triazinyl crystalline phase carbon nitride photocatalyst prepared from double precursors and application of triazinyl crystalline phase carbon nitride photocatalyst
CN116673058A